Offshore Platform Leg Integrity Assessment in the Gulf of Guinea - Charles Ugochukwu Orji; Samson Nitonye; Gerald Ahaneku (International Journal of Marine Engineering Innovation and Research, 2025)
Offshore platforms are large structures designed to accommodate personnel and equipment required for drilling wells in the seabed, extracting oil and/or natural gas, processing the resultant fluids, and transporting them to land by shipping or pipelines. Jacket platforms are fixed structures anchored to the seabed with piles to ensure stability against wind, wave, and current forces in the marine environment. The gradual deterioration of the fixed platform over time during operations becomes a subject of concern. The study aims to carry out a structural safety assessment (SSA) of an existing offshore platform in the Gulf of Guinea (GOG) by analyzing the reliability, risk index, safety margins, and structural integrity of the platform. A detailed investigation of design specifications, material characteristics, and environmental loads assessed the structural reliability and risk margins. A risk matrix prioritizes major structural concerns, resulting in specific recommendations for mitigation, repair, and maintenance. The platform's reserve strength ratio (RSR) was examined to build long-term structural integrity, safety, reliability, and environmental resilience strategies. The platform's safety and structural integrity were assessed using Ultimate Strength Assessment (USA) and Reliability–Risk Assessment (RRA) methods. According to the findings, corrosion, fatigue, seabed scour, subsidence, overload from environmental forces (wind, waves, currents, and earthquakes), collisions, crane accidents, explosions, falling objects, fires, leaks, accidental discharges, towing incidents, and well-related damage are the main threats to the jacket platform. The extent of corrosion and the associated probabilities of failure (POF) and reliability of the platform’s four jacket legs were calculated. The corrosion losses for Legs 1, 2, 3, and 4 were found to be 4.577%, 3.462%, 3.346%, and 4.039%, respectively. Leg 1 exhibited the highest POF (0.04577) and the lowest reliability (0.95423), whereas Leg 3 showed the lowest POF (0.03346) and the highest reliability (0.96654). The overall reliability factor of the platform was determined to be 1.0401, which, although lower than the safety load factor of 1.25, still indicates a level of structural safety. According to the risk matrix, all four jacket legs (L1–L4) fall within the “Medium” risk category for structural failure, suggesting the risk is within acceptable limits. To address corrosion-related risks specifically, cathodic protection is recommended as an effective mitigation and maintenance strategy. The Ultimate strength analysis produced an Ultimate strength of 3000 kN for a design capacity of 1250 kN, resulting in an RSR of 2.4, which is more than the minimum safety criterion of 1.50 for a manned structure, indicating that the jacket platform structure is SAFE and Fit-for-Purpose.